Frequency Locked Loop Based on the Time Nonrecursive Processing - Perisic, D. M.; Petrovic, V.; Kovacevic, B. (Engineering, Technology & Applied Science Research, 2018)
This paper describes one new approach to frequency locked loop (FLL), which is based on the time non-recursive processing of input periods. System parameters are defined by the ratio of frequencies. The conditions, under which the described system can have the properties of a FLL, are analyzed. All math analyses were made by the use of Z transform approach. It was shown that FLL is extremely fast and that it is suitable for usage in different predicting, tracking and modulation applications, for the measurements of frequency and for other applications. The FLL realization in the technique of standard integrated circuits is described. The oscilloscope picture, made on the realized 8 bit model, is presented. Analysis in frequency domain was made using Matlab tools.